Safe microsites for Symphoricarpos microphyllus (Caprifoliaceae) germination, a shrub species with seed dormancy - Martínez Orea, Yuriana; Castillo-Argüero, Silvia; Orozco-Segovia, Alma; Zavala-Hurtado, J. Alejandro; Bonilla-Valencia, Leticia (Instituto de Ecología, A.C., 2019)
Background and Aims: Temperate forests suffer continuous deforestation and other anthropogenic disturbances. Additionally, some types of forest management, such as secondary vegetation removal ("chaponeo"), can be another disturbance that negatively affects the values of some environmental variables important for seed germination. Light, soil temperature and moisture characterize microsites and determine germination percentages. These variables are also affected by slope orientation and vegetation structure. The aim of this study was to characterize microsites for Symphoricarpos microphyllus seed germination in a temperate forest, its response to light qualities in germination cameras, and seed viability during two years.Methods: Twenty-four microsites that differed according to their position in north/south (N/S) facing slopes, and by the presence/absence of secondary vegetation (“chaponeo”) due to forest management (U-undisturbed/P-perturbed) were characterized for light, soil temperature, moisture, pH and nitrogen. We also studied germination under different light qualities (white light, red light, far red light -FRL-, darkness) in germination cameras and seed viability for two years.Key results: All microsites were different in light, temperature and soil moisture. Microsites with the highest germination percentages were those US (undisturbed south) and UN (undisturbed north), where higher soil moisture and lower temperatures were registered, favoring embryo growth of seeds, since they possess morphophysiological dormancy. In cameras, germination percentages were the highest in FRL (32%). Seeds of S. microphyllus can remain viable for two years (60%).Conclusions: We do not recommend secondary vegetation removal because it affects variables of soil moisture (decreasing it) and temperature (increasing it) in microsites. This negatively influences this species germination, which needs a filtering of light and an alternation of high-low temperatures for dormancy breaking. These findings are important if we consider that the populations of this species are reducing due to overexploitation.